The reform of the EU's public procurement directives: a missed opportunity? - Van den Abeele, Eric (Brussels, 2012)
" This Working Paper provides a critical analysis of the EU Commission’s proposals to modernise and simplify its rules on public procurement. The author of the paper, Eric Van den Abeele, looks at the political background and reasons behind the EU’s revision of its public procurement directives. The reform aims at making the rules simpler and more flexible, providing better access to the public procurement market by SME’s and fostering a better qualitative use of public procurement through the introduction of social and environmental criteria.